POTENTIAL OF LAND AND BUILDING TRANSFER TAX (BPHTB) IN SEMARANG CITY - Silvia Hendrayanti; Cahyani Tunggal Sari (International Journal of Economics, Business and Accounting Research (IJEBAR), 2023)
Potential Tax Fees for Acquisition of Land and Building Rights This is a writing that describes the potential conditions and projections of BPHTB in Semarang City. BPHTB is considered to have potential as a source of regional revenue used to carry out development aimed at the welfare of all people. Based on the results of the discussion and data analysis carried out by the writing team, it can be concluded that the potential for BPHTB to contribute to the Semarang City Regional Revenue is within the medium criteria for 5 consecutive years from 2018 to 2022. Realization of BPHTB Tax against target in 4 years 2018, 2019 2020 and 2022 are considered very effective because they are above 100 percent. Meanwhile, in 2021 it is included in the less effective criteria because it is below 100 percent. This is understandable because of the possibility that the Covid 19 pandemic will have an influence on the realization of BPHTB taxes. Then, based on forecasting analysis in the next 4 years from 2023 - 2025, it is estimated that there will be an increase. For 2023, based on forecasting, the realization of BPHTB tax revenue will be IDR. 706,601,278,256 exceeds Bappeda's target of Rp. 675,000,000,000.